PENGARUH TERAPI TERTAWA TERHADAP TINGKAT DEPRESI PADA LANSIA DI PANTI UPTD GRIYA WREDA SURABAYA - Umamah, Farida; Hidayah, Latifah (Unusa Press, 2017)
The laughter therapy on the depression level experienced by the elderly in UPTD Panti Griya Wreda Surabaya. One of the psychological problems experienced by the elderly are prone to depression, but it can be prevented by laughter therapy. But, in reality there are still elderly who look sad, moody, or silent. There are various causes for such things, for instance, having not visit, thinking of his child and family. The objective of this study was to find out the effect of the laughter therapy on the depression level experienced by the elderly in UPTD Panti Griya Wreda Surabaya. The design of the study used the Pre Experiment with the approach of one group pretest-posttest design. The population of the elderly aged 60-69 years is 30 people, and the sample was 28 people taken by simple random sampling method. The independent variable is laughter therapy, whereas the dependent variable is the level of depression. The instrument used was a questionnaire sheet and SOP. Statistical test using Wilcoxon test with a significance of α = 0.05. The results of the study showed that before the laughter therapy nearly a half, 35.7% of the respondents experienced depression of medium level, and after the therapy nearly a half, 35.7 of the respondents was normal / did not experience depression. The result of Wilcoxon test on the laughter therapy showed the value of ρ = 0.000 and the value of α = 0.05 meaning that ρ < α then H0 is rejected, it means that the laughter therapy had an effect on the level of depression of the elderly in Panti UPTD Griya Wreda Surabaya. The conclusion of this study is that the more frequently the elderly followed the laughter therapy, the lower level of depression they experienced. Nurses are expected to resume activities of laugh therapy Griya Wreda Surabaya, that elderly people are motivated to do this on a regular basis and in groups.